THE ANTIBACTERIAL PROPERTIES OF MODIFIED BENTONITE DEPOSIT TAM BO - Bui Quang; Aleksandr Vezentsev; Vladimir Bukhanov; Pavel Sokolovsky; Mariya Mihaylyukova (Belgorod National Research University, 2016)
In this article, the antibacterial properties enriched bentonite Tam Bo deposit, Lam Dong Province (Vietnam) modified in various ways: alkali - by processing enriched bentonite LiOH solution at a temperature of 60°C for 30 min, brine - by processing enriched bentonite, 3% solution of Na2CO3 at 55°C for 30 min, and nanoparticles of silver - silver nanoparticles by immobilizing on the surface of the bentonite by precipitation of silver nanoparticles AgNO3 solution. Initially, the bentonite clay deposits Tam Bo contains 40 - 60 wt% of active sorptionmontmorillonite. Enrichment, followed by modifying the content of montmorillonite can increase up to 70 - 80 wt. %. The modification allows the bentonite increase in its physical-chemical and colloid-chemical characteristics to 2 - 3 times, such as degree of swelling, the specific surface area, cation exchange capacity. The experimental data showed that the bentonite modified with silver nanoparticles can effectively inhibit the growth of opportunistic pathogens like Enterococcus feacalis, Escherichia coli, Proteus mirabilis, Pseudomonas aerugenosa, Salmonella typhimurium, Staphylococcus aureus and Candida albicans. Modification of bentonite clay and montmorillonite crystal lattice is included in its composition with silver nanoparticles allows increasing the bactericidal activity against aflatoxin to 65 times.